2002
DOI: 10.1254/jjp.88.77
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Protease-Activated Receptor-2 Deficiency on Allergic Dermatitis in the Mouse Ear

Abstract: ABSTRACT-To investigate the involvement of protease-activated receptor-2 (PAR-2) in allergic dermatitis, we generated PAR-2-deficient (PAR-2) mice. Ear thickness, contact hypersensitivity (CH) induced by topical application of picryl chloride (PC) or oxazolone (Ox) after sensitization, and vascular permeability after ear passive cutaneous anaphylaxis (PCA) were compared between wild-type (WT) and PAR-2

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
58
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 89 publications
(62 citation statements)
references
References 43 publications
4
58
0
Order By: Relevance
“…These studies, combined with the early observation of increased PAR-2 mRNA expression following cytokine pre-treatment of vascular endothelial cells (21), strongly suggested a role for PAR-2 in the integration of vascular inflammation. Similar mechanisms may be responsible in our observation on contact-induced skin inflammation, which was abrogated in PAR-2-gene-deficient mice (22). Another line of evidence for PAR-2 in association with chronic inflammation was demonstrated in an adjuvant monoarthritis model (23).…”
Section: Physiological Studies Using Par-2-gene-deficient Micesupporting
confidence: 88%
“…These studies, combined with the early observation of increased PAR-2 mRNA expression following cytokine pre-treatment of vascular endothelial cells (21), strongly suggested a role for PAR-2 in the integration of vascular inflammation. Similar mechanisms may be responsible in our observation on contact-induced skin inflammation, which was abrogated in PAR-2-gene-deficient mice (22). Another line of evidence for PAR-2 in association with chronic inflammation was demonstrated in an adjuvant monoarthritis model (23).…”
Section: Physiological Studies Using Par-2-gene-deficient Micesupporting
confidence: 88%
“…The inability of OVX to increase the CHS response may be due to maximization of ear thickness, since the maximal change possible appears to be about 0 . 11 mm (Kawagoe et al 2002) and ear thickness observed in our study was about 0 . 1 mm, and thus was already at the top of the range.…”
Section: Resultssupporting
confidence: 50%
“…Particularly, in the respiratory system, PAR2 is abundantly expressed in the epithelial cells, and its activation by the endogenous and exogenous proteinases leads to release of pro-inflammatory mediators including cyto-kines and prostanoids (10 -12). It is also to be noted that the pro-inflammatory role of PAR2 has been well described in the gastrointestinal tract (13), kidney (14), skin (15), synovial joints (16), and so on.…”
Section: Introductionmentioning
confidence: 99%